Kajian Konsep Pendidikan Multikultural dalam Islam - Arif Muzayin Shofwan (Pendidikan Agama Islam STIT Palapa Nusantara, 2022)
Some experts claim that multicultural education comes from the West, especially from the United States which only knows blacks and whites. However, this statement has been strongly denied by other experts. In Islam, actually multicultural education has existed since the time of the Prophet Muhammad. Research with this literature study resulted in the following conclusions. First, Islam has recognized multicultural education since the time of the Prophet Muhammad SAW, namely Islam does not recognize the existence of a class system, because it is not in accordance with its character, but there is only one level where all individuals have the same rights and obligations. Second, in the context of Indonesia, the foundation for multicultural education is Pancasila and the 1945 Constitution. Third, the characteristics of multicultural education in Islam have three characteristics, namely: (1) principles, justice, & fairness; (2) the principle of humanity, togetherness, and peace; and (3) develop an attitude of acknowledging, accepting, and appreciating cultural diversity, which is based on the Qur'an and the Hadith of the Prophet Muhammad.